Polar Shift: Charge carrier polarization energies in organic electronic materials - Kaklamanis, K.; Papageorgiou, D.G. (Computer physics communications, 2025)
Electronic polarization of charge carriers in the solid state plays an important role in organic electronics, as it alters the gas phase energy levels associated with phenomena such as charge transport, molecular doping, charge injection and charge separation at interfaces. In this article we present Polar Shift, a software package for calculating the polarization energy of an electron or hole charge carrier in organic electronic materials. The software uses an atomistic approach employing the microelectrostatics model. Molecular charge distributions are represented by atomic point charges, while the molecular polarizability is divided into distributed atomic contributions. The electrostatic and inductive components of the polarization energy are calculated separately. For the electrostatic interactions we propose an efficient cutoff–based scheme that allows fast yet accurate evaluation of the relevant energy. For the induction part we use a self–consistent iterative method based on modified field interaction tensors in the framework of the Thole model. Polar Shift can be applied to ideal molecular crystals, thermally disordered crystalline packings or completely amorphous materials. Many additional features are implemented such as calculation of the molecular polarizability tensor, fitting of molecular polarizabilities to reference values, different schemes for computing induction energies, and extrapolation of induction energies to the bulk limit. Special attention has been paid to the interoperability with other software packages, so Polar Shift can obtain the required input from various widely used file types such as pdb, mol2 or even binary dcd files. The software is parallelized using the MPI standard thus exploiting a wide range of shared and distributed memory computer architectures. Polar Shift is applied to eight different test cases of prototype organic electronics materials demonstrating its capabilities, and the results are compared with existing literature. Program Title: Polar Shift CPC Library link to program files:https://doi.org/10.17632/26ck9stzh9.1 Developer's repository link:http://cmsl.materials.uoi.gr/polar-shift Licensing provisions: GPLv2 Programming language: Fortran 2008 Supplementary material: User manual (45 pages), 22 annotated examples with reference output, input and output files for the eight test cases described in the paper. Nature of problem: Electronic polarization of charge carriers in organic electronic materials is responsible for altering key quantities from their gas phase counterparts. In many molecular solids electron affinities and ionization potentials are severely affected, with the corresponding energy shifts reaching values of the order of ≈1 eV [1]. This suggests that polarization should be taken into account in phenomena such as charge transport, molecular doping, charge injection and charge separation at interfaces [2]. In addition, there is an ever–increasing demand for specialized, yet easy to use, computational tools to be used in the prediction and investigation of materials properties. Solution method: The classical atomistic microelectrostatics [3] (or alternatively known as polarizable point dipoles [4]) model is used. Atoms are represented by point charges reproducing the molecular electrostatic potential, while point dipoles are induced at each atomic site. The molecular polarizability tensor is represented by isotropic distributed atomic polarizabilities. By employing the zero overlap approximation the two contributions in polarization energy, namely electrostatic and induction, can be separately evaluated. Electrostatic interactions are calculated using a cutoff–based algorithm and automatic replication of the simulation cell where necessary. Induced dipole conformation in the system is determined self consistently using a successive over–relaxation algorithm, based on modified field interaction tensors in the framework of the Thole model [5]. The latter allows for short range interaction screening, thus avoiding the well known polarization catastrophe. Two different schemes are implemented to calculate induction in the condensed phase. (a) Dipole conformation is obtained by applying periodic boundary conditions and a truncation cutoff for intermolecular interactions. (b) A finite spherical cluster centered at the charged molecule is extracted from the simulation cell. Since in both cases the calculated induction energies depend on the truncation distance, an extrapolation method can be applied to retrieve the bulk limit. Additional comments including restrictions and unusual features: There are no restrictions on the number of molecules in the simulation cell, the only limit being computer memory. The software can read various widely used file formats, making it interoperable with other packages. Arbitrary simulation cells may be specified using cell lengths and angles. Assignment of atomic polarizabilities in large molecular structures can be assisted by selecting values from predefined sets, based on atomic element, type or index. Parallelization using MPI exploits shared or distributed memory computer architectures. [1]N. Sato, K. Seki, H. Inokuchi, Polarization energies of organic solids determined by ultraviolet photoelectron spectroscopy, J. Chem. Soc. Faraday Trans. II 77 (1981) 1621, https://doi.org/10.1039/F29817701621[2]G. D'Avino, L. Muccioli, F. Castet, C. Poelking, D. Andrienko, Z.G. Soos, J. Cornil, D. Beljonne, Electrostatic phenomena in organic semiconductors: fundamentals and implications for photovoltaics, J. Phys. Condens. Matter 28 (2016) 433002, https://dx.doi.org/10.1088/0953-8984/28/43/433002[3]P. Ren, C. Wu, J.W. Ponder, Polarizable atomic multipole-based molecular mechanics for organic molecules, J. Chem. Theory Comput. 7 (2011) 3143–3161, https://doi.org/10.1021/ct200304d.[4]J. Sala, E. Guàrdia, M. Masia, The polarizable point dipoles method with electrostatic damping: implementation on a model system, J. Chem. Phys. 133 (2010) 234101, https://doi.org/10.1063/1.3511713.[5]B.T. Thole, Molecular polarizabilities calculated with a modified dipole interaction, Chem. Phys. 59 (1981) 341, https://doi.org/10.1016/0301-0104(81)85176-2